Exploring Elementary Teacher’s Understanding and Classroom Practices in Fostering Students’ Emotional Intelligence in Myanmar - Hlaing, Nwaye Nwaye (Indonesian Journal of Teaching and Teacher Education, 2025)
This study explores Myanmar elementary school teachers’ understanding of emotional intelligence (EI) and the classroom practices they use to foster students’ EI within the challenging educational context following the 2021 military coup, which disrupted schooling, limited resources, and created emotionally demanding environments. Employing a qualitative phenomenological design, data were collected through semi-structured interviews with twelve elementary school teachers from public, private, and community schools across six regions in Myanmar. The data were analysed using thematic analysis guided by Goleman’s (1995) five components of emotional intelligence: self-awareness, self-regulation, motivation, empathy, and social skills. The findings indicate that teachers demonstrate a partial yet practical understanding of EI and apply various classroom strategies, including integrating emotional learning into academic subjects, using positive communication, promoting cooperative learning activities, and encouraging students’ self-expression. Teachers perceived these practices as contributing to improvements in students’ behaviour, learning motivation, academic performance, and social interaction. Furthermore, EI-based approaches were reported to strengthen teacher–student relationships, improve classroom management, and enhance teachers’ job satisfaction. However, teachers also faced challenges such as limited instructional time, a lack of formal training in emotional intelligence, and contextual constraints related to political instability and scarce educational resources. Overall, the study concludes that fostering emotional intelligence in Myanmar elementary classrooms is essential for students’ holistic development and teachers’ professional effectiveness, underscoring the need for systematic teacher training and policy support to integrate emotional intelligence into everyday teaching practices.